The minority concept in the Turkish context : practices and perceptions in Turkey, Greece, and France - Akgönül, Samim. (Muslim Minorities, 2013)
In The Minority Concept in the Turkish Context , Samim Akgönül presents a conceptual discussion of the term 'minority' from various perspectives, most notably history, sociology and political science. The concept of minority has a specific understanding in the Turkish political, sociological and legal context due to the Ottoman Millet system approach. The conceptual discussion is illustrated by three case studies: religious minorities in Turkey that are the result of the elimination policies during the Turkish nation building process, Muslim minorities in Greece as heritage of the Ottoman domination until the 20th century, and new minorities originating from Turkey and living in France as the result of the Turkish immigration of 1960's and following decades.